(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
The increasing consumption of sugary beverages and ultra-processed foods among children has emerged as a major public health concern worldwide, particularly due to its detrimental effects on oral health. Hard dental tissues, including enamel and dentin, are especially vulnerable during childhood, when mineralization processes are still ongoing. Excessive intake of free sugars, acidic additives, and refined carbohydrates contributes to the development of dental caries, enamel erosion, hypomineralization, and increased tooth sensitivity. This article provides a comprehensive analysis of the mechanisms by which sugary drinks and ultra-processed foods affect hard dental tissues in children and explores contemporary approaches to improving prevention and treatment strategies. Emphasis is placed on dietary modification, early risk assessment, fluoride-based and biomimetic remineralization therapies, minimally invasive restorative techniques, and interdisciplinary preventive programs. Strengthening these strategies is essential to reduce the burden of dental diseases and improve long-term oral health outcomes in the pediatric population.